2000
DOI: 10.4141/a99-065
|View full text |Cite
|
Sign up to set email alerts
|

Canola screenings as a fiber source in barley-based feedlot diets: effects on rumen fermentation and performance of steers

Abstract: . 2000. Canola screenings as a fiber source in barley-based feedlot diets: effects on rumen fermentation and performance of steers. Can. J. Anim. Sci. 80: [161][162][163][164][165][166][167][168]. Two experiments were conducted to determine the feeding value of canola screenings in combination with barley grain for beef steers. Four dietary treatments were used. These included canola screenings:barley grain ratios of 100:0; 75:25, 50:50, and 25:75 (as-fed basis). In a metabolic trial, the effects of dietary tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…The primary reasons for the lower digestibility are not known and could be attributed to (1) high lignin content in some of the byproduct feeds, (2) small particle size of the feeds within the high-lipid high-fibre byproduct pellets, and (3) negative associative effects of the lipid on rumen fermentation. Similar findings were also seen previously (Pylot et al 2000) where canola screenings were used to replace a substantial portion of barley grain resulting in lower ADG and G:F.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The primary reasons for the lower digestibility are not known and could be attributed to (1) high lignin content in some of the byproduct feeds, (2) small particle size of the feeds within the high-lipid high-fibre byproduct pellets, and (3) negative associative effects of the lipid on rumen fermentation. Similar findings were also seen previously (Pylot et al 2000) where canola screenings were used to replace a substantial portion of barley grain resulting in lower ADG and G:F.…”
Section: Discussionsupporting
confidence: 75%
“…As a consequence of increased grain prices, feedlot operators have been searching for viable alternatives to cereal grain as energy sources for finishing cattle. Studies evaluating the use of byproducts from the cereal grain, oilseed, and bioethanol industries for finishing cattle have demonstrated that comparable carcass quality and average daily gain (ADG) can be attained, relative to barley grain, although the inclusion rate of the byproducts in diets may affect performance (Pylot et al 2000;Amat et al 2012;Yang et al 2012). Most previous studies have investigated dietary byproduct inclusion in isolation rather than utilizing a combination of byproducts.…”
Section: Introductionmentioning
confidence: 99%
“…Elliot et al (1997) reported that replacing corn starch with different sources of fat resulted in an increase in ruminal pH. Similar results were reported in cannulated steers when canola screenings replaced barley grain (Pylot et al 1999b). When fermentation of carbohydrate occurs, protons are released, thus decreasing pH; however, fat sources with high degree of unsaturated fatty acids capture protons when they are hydrogenated in the rumen (Doreau and Chilliard 1997).…”
Section: Ruminal Phsupporting
confidence: 54%
“…(1 (Moore et al 1986;Brandt 1995;Pylot et al 1999b). In the current study, the average dietary fat intake on the HF diets was 715 g d (1 .…”
Section: Apparent Nutrient Digestibility Coefficientsmentioning
confidence: 99%
See 1 more Smart Citation